2011
DOI: 10.1016/j.alcohol.2010.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine dynamics associated with, and resulting from, schedule-induced alcohol self-administration: analyses in dopamine transporter knockout mice

Abstract: Preclinical and clinical evidence suggest an association between alcoholism and the primary regulator of extracellular dopamine concentrations, the dopamine transporter (DAT). However, the nature of this association is unclear. We determined if ten days of voluntary alcohol self-administration followed by withdrawal could directly alter DAT function, or if genetically-mediated changes in DAT function and/or availability could influence vulnerability to alcohol abuse. Heterozygous (DAT+/-) and homozygous mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 62 publications
3
32
0
1
Order By: Relevance
“…Because of its characteristics of 'excessiveness' and 'persistence', SIP has been used as a model for compulsive responding in OCD, schizophrenia, alcohol abuse and predisposition to drug addiction (Gilpin et al 2008;Hawken et al 2011;Mittleman et al 2003Mittleman et al , 2011Myracle et al 2005; for review, Platt et al 2008;Rosenzweig-Lipson et al 2007;Schechter et al 2008;Wayner 2002). Moreover, chronic psychiatric inpatients frequently engage in psychogenic polydipsia (de Leon et al 1994(de Leon et al , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its characteristics of 'excessiveness' and 'persistence', SIP has been used as a model for compulsive responding in OCD, schizophrenia, alcohol abuse and predisposition to drug addiction (Gilpin et al 2008;Hawken et al 2011;Mittleman et al 2003Mittleman et al , 2011Myracle et al 2005; for review, Platt et al 2008;Rosenzweig-Lipson et al 2007;Schechter et al 2008;Wayner 2002). Moreover, chronic psychiatric inpatients frequently engage in psychogenic polydipsia (de Leon et al 1994(de Leon et al , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in SIP, the substitution of water for ethanol solution-induced equivalent levels of consumption has been considered as a promising behavioral model of alcohol abuse, relating directly to the induction of compulsive alcohol drinking (Gilpin et al 2008;Mittleman et al 2003Mittleman et al , 2011Singer et al 1982;Singer and Wallace 1984;Wayner 2002). Schedule induction and ethanol polydipsia provide an opportunity to investigate the development of drinking typologies that lead to chronic, excessive voluntary alcohol consumption in animals (Colotla 1981;Falk and Tang 1988), as well as the neural substrates and pharmacology of alcohol addiction (Escher and Mittleman 2006;Mittleman et al 2011).…”
Section: The Sip Proceduresmentioning
confidence: 99%
“…Because of its characteristics of "excessiveness" and "persistence," growing evidence points to schedule-induced polydipsia (SIP) as a candidate model for the study of neuropsychiatric disorders presenting with compulsive behavior such as OCD, schizophrenia (Hawken et al 2011;Rosenzweig-Lipson et al 2007;Schechter et al 2008;Woods-Kettelberger et al 1997; for review, see Platt et al 2008), and alcohol abuse (Gilpin et al 2008;Mittleman et al 2003Mittleman et al , 2011Wayner 2002). The SIP model is characterized by the development of an adjunctive behavior of excessive drinking in food-deprived animals exposed to intermittent food-reinforcement schedules (Falk 1961(Falk , 1971.…”
Section: Introductionmentioning
confidence: 99%
“…Destruction of dopamine terminals within the mesolimbic dopamine circuitry (i.e., nucleus accumbens and olfactory tubercle) in rats via bilateral 6-hydroxydopamine lesions prevented acquisition of water SIP (Robbins & Koob, 1980). Mice with a genetically engineered deletion of the dopamine transporter (DAT) exhibited a diminished acquisition of ethanol SIP with access to a 5% solution (Mittleman et al, 2011), although earlier work with a two-bottle choice procedure showed that neither male nor female DAT knockout mice displayed differences in ethanol consumption versus wild-type controls when a comparable 4% solution was offered (Hall, Sora, & Uhl, 2003). The apparent disparity between these observations may reflect the differential roles of dopaminergic signaling in the context of non-regulatory (SIP) versus regulated (two-bottle choice) ethanol consumption, similar to differences noted for adjunctive versus deprivation-induced water drinking following destruction of dopamine terminals within the mesolimbic pathway (Robbins & Koob, 1980).…”
Section: Significant Biological and Environmental Factors That Comentioning
confidence: 99%